Core–Shell Bi2Se3@mSiO2‐PEG as a Multifunctional Drug‐Delivery Nanoplatform for Synergistic Thermo‐Chemotherapy with Infrared Thermal Imaging of Cancer Cells. (27th November 2017) - Li, Zhuo; Li, Zhenglin; Sun, Lei; Du, Baosheng; Wang, Yuanlin; Zhao, Gongyuan; Yu, Dengfeng; Yang, Sisi; Sun, Ye; Yu, Miao
Abstract: Thermo‐chemotherapy combining photothermal therapy (PTT) with chemotherapy has become a potent approach for antitumor treatment. In this study, a multifunctional drug‐delivery nanoplatform based on polyethylene glycol (PEG)‐modified mesoporous silica‐coated bismuth selenide nanoparticles (referred to as Bi2 Se3 @mSiO2 ‐PEG NPs) is developed for synergistic PTT and chemotherapy with infrared thermal (IRT) imaging of cancer cells. The product shows no/low cytotoxicity, strong near‐infrared (NIR) optical absorption, high photothermal conversion capacity, and stability. Utilizing the prominent photothermal effect, high‐contrast IRT imaging and efficient photothermal killing effect on cancer cells are achieved upon NIR laser irradiation. Moreover, the successful mesoporous silica coating of the Bi2 Se3 @mSiO2 ‐PEG NPs cannot only largely improve the stability but also endow the NPs high drug loading capacity. As a proof‐of‐concept model, doxorubicin (DOX) is successfully loaded into the NPs with rather high loading capacity (≈50.0%) via the nanoprecipitation method. It is found that the DOX‐loaded NPs exhibit a bimodal on‐demand pH‐ and NIR‐responsive drug release property, and can realize effective intracellular drug delivery for chemotherapy. The synergistic thermo‐chemotherapy results in a significantly higher antitumor efficacy than either PTT or chemotherapy alone. The work reveals the great potential of such core–shell NPs as a multifunctional drug‐delivery nanosystem for thermo‐chemotherapy. Abstract : Bi2 Se3 @mSiO2 ‐PEG NPs, a multifunctional drug‐delivery nanoplatform based on polyethylene glycol (PEG)‐modified mesoporous silica‐coated bismuth selenide nanoparticles is developed for synergistic photothermal therapy and chemotherapy together with infrared thermal imaging of cancer cells. The work reveals the great potential of such core–shell nanoparticles (NPs) as a multifunctional drug‐delivery nanosystem for thermo‐chemotherapy.